PELAKSANAAN PENDIDIKAN ANTI KORUPSI DALAM PEMBELAJARAN PAI DI SDN NAGASARI 2 KARAWANG - Nurul Aulia; Nazwa Nur Aulia Syam; Fathin Ihsanul Haq; Naila Hanastasya Adzikry; Hisa Fakhriya; Siti Nabilah; Fawwas Hafish Harsoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the implementation of anti-corruption education in Islamic Religious Education (IRE) classes at SDN Nagasari 2. The background of this study is based on the importance of instilling anti-corruption values from an early age through education, particularly through IRE classes that teach the values of honesty, responsibility, discipline, and trust. This study employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The research subjects consist of PAI teachers, the school principal or vice principal, and students at SDN Nagasari 2. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using the Miles and Huberman model. The results of the study indicate that the implementation of anti-corruption education at SDN Nagasari 2 has been integrated into PAI instruction through the instillation of values such as honesty, responsibility, discipline, and trust, which are linked to verses from the Qur’an, hadiths, and the exemplary traits of the Prophet. PAI teachers implement anti-corruption education by fostering positive behavior, issuing reprimands, and applying educational sanctions to students who violate school regulations. Nevertheless, several challenges remain, such as a lack of student discipline, cheating, tardiness, and a lack of responsibility toward their assignments. Therefore, anti-corruption education at Islamic Religious Education teachers implement anti-corruption education by fostering positive behavior, issuing warnings, and imposing educational sanctions on students who violate school rules. However, there are still several challenges, such as a lack of student discipline, cheating, tardiness, and a lack of responsibility toward their assignments. Therefore, anti-corruption education in Islamic Religious Education (IRE) plays a crucial role in shaping students’ character to foster honesty and noble moral values.